When Christmas comes again : the World War I diary of Simone Spencer - Levine, Beth Seidel (New York : Scholastic Inc., 2002)
Teenage Simone's diaries for 1917 and 1918 reveal her experiences as a carefree member of New York society, then as a "Hello girl," a volunteer switchboard operator for the Army Signal Corps in France.
Keywords: United States. -- Army. -- Signal Corps -- Fiction; World War, 1914-1918 -- France -- Juvenile fiction; World War, 1914-1918 -- France -- Fiction; World War, 1914-1918 -- United States -- Fiction; World War, 1914-1918 -- New York (State) -- Juvenile fiction; Social classes -- Fiction; Diaries -- Fiction; New York (N.Y.) -- History -- Fiction